2023
DOI: 10.2147/ijgm.s395881
|View full text |Cite
|
Sign up to set email alerts
|

FNBP4 is a Potential Biomarker Associated with Cuproptosis and Promotes Tumor Progression in Hepatocellular Carcinoma

Abstract: Background Hepatocellular carcinoma (HCC) is one of the most common malignant tumors that lacks an efficient therapeutic approach because of its elusive molecular mechanisms. This study aimed to investigate the biological function and potential mechanism of formin-binding protein 4 (FNBP4) in HCC. Methods FNBP4 expression in tissues and cells were detected by quantitative real-time PCR (qRT‒PCR), Western blot, and immunohistochemistry (IHC). The Kaplan-Meier method was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…FNBP4 is associated with the TCA process of cuproptosis. After data analysis, it was found that the expression of FNBP4 in liver cancer increased significantly, and a high expression of FNBP4 was negatively correlated with the patient’s OS [ 78 ]. A cuproptosis-related gene (CRG) model was constructed by Ke, C. et al Through clinical sample qPCR and immunohistochemical detection, it was determined that DLAT had a cancer-promoting effect, which was significantly upregulated in liver cancer and promoted HepG2 and Huh7 cell proliferation, migration, and invasion [ 79 ].…”
Section: Value Of Cuproptosis Combined With Ferroptosis In Predicting...mentioning
confidence: 99%
“…FNBP4 is associated with the TCA process of cuproptosis. After data analysis, it was found that the expression of FNBP4 in liver cancer increased significantly, and a high expression of FNBP4 was negatively correlated with the patient’s OS [ 78 ]. A cuproptosis-related gene (CRG) model was constructed by Ke, C. et al Through clinical sample qPCR and immunohistochemical detection, it was determined that DLAT had a cancer-promoting effect, which was significantly upregulated in liver cancer and promoted HepG2 and Huh7 cell proliferation, migration, and invasion [ 79 ].…”
Section: Value Of Cuproptosis Combined With Ferroptosis In Predicting...mentioning
confidence: 99%